PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA KORUPSI DALAM PENYIMPANGAN PENYERAPAN ANGGARAN APBD PADA BELANJA HIBAH KABUPATEN BENGKALIS (STUDI PUTUSAN NO 4/PID.SUS.TPK/2017/PN.PBR).” - Taufiqqul Hidayat; Mexsasai Indra; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Grant fund corruption can occur because of the abuse of power by the authorities. The number of cases of corruption in the absorption of the grant spending APBD that occurred in Bengkalis Regency is quite high. If you look at the criminal cases of corruption, especially in the irregularities in the absorption of the APBD, grant spending committed by unscrupulous members of the DPRD actually involves many parties. The money received was intended for the defendant to fight for an additional budgetary amount included in the grant funds in the Bengkalis Regency APBD. However, in the process of asking for accountability of perpetrators of criminal acts of corruption, especially in irregularities in the absorption of the APBD, grant expenditures are not carried out thoroughly.This type of research can be classified in the type of sociological legal research (empirical), because in this study the author directly conducted research at the location or place being studied in order to provide a complete and clear picture of the problem under study. This research was conducted in the legal area of Bengkalis Regency. The data sources used are primary data and secondary data. Data collection techniques in this study were interviews and literature review.The conclusions that can be obtained from the results of the research are First, the criminal responsibility of the perpetrators of Corruption in the Absorption of APBD Budget on the Bengkalis Regency grant expenditure (Study of Decision No.4 / Pid.Sus.TPK / 2017 / PN.PBR) involves many parties. The party held accountable is only one perpetrator. However, in the process of asking for accountability of perpetrators of criminal acts of corruption, especially in irregularities in the absorption of the APBD, grant expenditures are not carried out thoroughly. Second, Constraints in holding criminal accountability for the perpetrators of Corruption in the Absorption of APBD Budget in Bengkalis Regency grant expenditures related to the results of assets from criminal acts committed are very difficult for its flow to be traced. So that the parties involved are difficult to hold criminal responsibility. Keywords: Criminal Accountability, Corruption, Grant Expenditures